'True and fair view' versus 'Present fairly in conformity with generally accepted accounting principles' - Kirk, N. E. (Massey University, 2001)
The ‘true and fair view’ concept is one of two competing but not mutually exclusive legal standards for financial reporting quality that have been subject to debate on their meaning, use and importance. The other is ‘present fairly in conformity with generally accepted accounting principles’ (GAAP). While the former is closely identified with judgement and is used in the United Kingdom, the European Union, Singapore, Australia, and New Zealand, the latter is the standard for United States financial reporting and tends to be more rule based. This paper presents the findings of an empirical investigation of the ‘true and fair view’ in New Zealand. It reports the results of a survey of financial directors, auditors and shareholders of New Zealand listed companies investigating their perceptions of, and preferences for, ‘true and fair view’ versus other standards for financial statement reporting including ‘present fairly in conformity with generally accepted accounting principles’ (GAAP), 'fairly reflects' and 'present fairly', and compares the findings with relevant international research. The purpose of the research was twofold; firstly to determine if ‘within-group’ and ‘betweengroup’ differences in perceptions and preferences for the terms existed, thus contributing to an expectations gap; and, secondly, to examine whether or not the New Zealand respondents shared the preference for ‘true and fair view’ versus ‘present fairly in conformity with GAAP’ found in previous international research. The results show that a clear majority of all three groups share similar perceptions of the meaning of the 'true and fair view’ concept, and support its use in financial reporting. All groups preferred ‘true and fair view’ to other terms including ‘fairly present in conformity with GAAP’, a result consistent with previous comparisons of United Kingdom, and United States investors’ opinions. This illustrates that the 'true and fair view' concept remains an important international overall standard for financial reporting quality.
Keywords: Financial statements; Disclosure (Accounting)